2012
DOI: 10.3174/ajnr.a3251
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Disruption after Cardiac Surgery

Abstract: Background and purpose CNS complications are often seen after heart surgery, and post-surgical disruption of the blood-brain barrier (BBB) may play an etiologic role. The objective of this study was to determine the prevalence of MRI-detected BBB disruption (Hyperintense Acute Reperfusion Marker: HARM) and DWI lesions after cardiac surgery. Materials & methods All patients had an MRI after cardiac surgery. In half the patients (group 1), we administered gadolinium 24 hours after surgery and obtained high-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 36 publications
0
78
0
Order By: Relevance
“…Severe BCSFB disruption defined sulcal gadolinium enhancement or subarachnoid hemorrhage apparent across 10 adjacent slices. 15 A representative case of severe BCSFB disruption is shown in Figure 1B.…”
Section: Image Analysis Of Gve and Bcsfb Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe BCSFB disruption defined sulcal gadolinium enhancement or subarachnoid hemorrhage apparent across 10 adjacent slices. 15 A representative case of severe BCSFB disruption is shown in Figure 1B.…”
Section: Image Analysis Of Gve and Bcsfb Disruptionmentioning
confidence: 99%
“…Overall, 60 patients with a median (interquartile range) National Institutes of Health Stroke Scale score 18 (15)(16)(17)(18)(19)(20)(21)(22) at admission were included in the study. A total of 28 patients (47%) received systemic r-tPA before MT.…”
Section: Baseline Traits Of the Included Populationmentioning
confidence: 99%
“…Systemic inflammation due to sepsis and surgery can disrupt the blood-brain barrier (16,24), and elevated levels of pro-inflammatory cytokines in the brain have pathological effects on neural function (15,22). It is well known that pro-inflammatory cytokines modulate synaptic plasticity (15,22) including long-term potentiation (LTP), which is considered the cellular basis of learning and memory (2, 18).…”
mentioning
confidence: 99%
“…Delirium is a major problem after CABG surgery with the approximate reported incidence rate of 20-80% [2]. This complication is associated with increased mortality, longer hospital stay, increased hospital costs, and long-term care [2,3,4]. Regarding the high incidence of delirium in patients undergoing CABG surgery, prophylactic treatment is preferable.…”
mentioning
confidence: 99%
“…Regarding the high incidence of delirium in patients undergoing CABG surgery, prophylactic treatment is preferable. Hence, pharmacological neuroprotective strategies have been developed for these patients [3,4]. A meta-analysis indicated that preoperative low-dose and short-term administration of haloperidol or risperidone may modestly reduce delirium occurrence in high-risk patients that need intensive care unit (ICU) [4].…”
mentioning
confidence: 99%